2021
DOI: 10.3390/w13040422
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Watershed Delineation and Climate Datasets Density on Runoff Predictions for the Upper Mississippi River Basin Using SWAT within HAWQS

Abstract: The quality of input data and the process of watershed delineation can affect the accuracy of runoff predictions in watershed modeling. The Upper Mississippi River Basin was selected to evaluate the effects of subbasin and/or hydrologic response unit (HRU) delineations and the density of climate dataset on the simulated streamflow and water balance components using the Hydrologic and Water Quality System (HAWQS) platform. Five scenarios were examined with the same parameter set, including 8- and 12-digit hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 63 publications
2
15
0
Order By: Relevance
“…The reason is because the capacities to capture the important features of the watersheds and variation of rainfall regime of the coarse watershed delineation are better than those of the fine one. This argument is somewhat against the argument in the study in the Upper Mississippi River Basin, USA (Chen et al 2021).…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…The reason is because the capacities to capture the important features of the watersheds and variation of rainfall regime of the coarse watershed delineation are better than those of the fine one. This argument is somewhat against the argument in the study in the Upper Mississippi River Basin, USA (Chen et al 2021).…”
Section: Introductionmentioning
confidence: 77%
“…In this case, the trends of changes were not consistent for every water balance component, particularly in ET (Chaplot 2014). Another study in the 4,91,700-km 2 Upper Mississippi River Basin, USA, found that the simulation results of surface runoff, lateral flow, groundwater flow, and water yield (WYLD) increased approximately 0.98, 92, 2.73, and 2.07%, respectively, when the number of sub-watersheds and HRUs increased (Chen et al 2021).…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations